EFFECTIVENESS OF THE ONLINE LEARNING PROCESS ON MACHINING ENGINEERING LEARNING IN SMK NEGERI 2 TASIKMALAYA CITY - Husain, Wahyu Arief; Yayat, Yayat; Komaro, Mumu (Universitas Pendidikan Indonesia, 2023)
ABSTRACTThe world is currently experiencing the Covid-19 pandemic including Indonesia. The Covid19 pandemic has had an impact on the education sector, resulting in the change of the learning system that is usually face-to-face now to remote through online learning systems. So based on these circumstances, information is needed about the effectiveness of the online learning process during the Covid19 pandemic. This research aims to find out the effectiveness of aspects of the online learning process, namely learning planning, learning activities, learning strategies, media and learning technology, and assistance services by adjusting the achievement to online learning standards based on the experience of students doing online learning during the Covid-19 pandemic. The research methods used are descriptive methods and the data is obtained by survey. The subject of this study was a student of class X machining SMK Negeri 2 Tasikmalaya Year of Study 2020/2021 who experienced online learning during the Covid-19 pandemic. This study sample was as many as 100 students of class X Machining. The instrument used is an online learning process quality standard instrument derived from the SPADA Online Learning Process Guide 2019 by Kemenristekdikti. The result of this research is, the online learning process is quite effective, including media and learning technology, learning activities, learning strategy aspects, and aspects of learning planning are in the category of quite effective, while the aspect of learning assistance services is in the ineffective category.